2005
DOI: 10.1146/annurev.physiol.67.031103.153004
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR PHYSIOLOGY OF INTESTINAL N+/H+ EXCHANGE

Abstract: The sodium/hydrogen exchange (NHE) gene family plays an integral role in neutral sodium absorption in the mammalian intestine. The NHE gene family is comprised of nine members that are categorized by cellular localization (i.e., plasma membrane or intracellular). In the gastrointestinal (GI) tract of multiple species, there are resident plasma membrane isoforms including NHE1 (basolateral) and NHE2 (apical), recycling isoforms (NHE3), as well as intracellular isoforms (NHE6, 7, 9). NHE3 recycles between the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
385
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(393 citation statements)
references
References 164 publications
5
385
1
2
Order By: Relevance
“…This indicated that NHE gene regulation may be species specific. However, no careful quantitation of the amount of NHE-2 protein along the horizontal intestinal axis has been reported (Zachos et al, 2005). The different distribution of transporters along the intestinal axis from proximal to distal may be due to the unique morphological characteristics of the intestine and substrates, even though further research is needed to confirm this.…”
Section: Mgttvlnlqprarrflpeqfskkapqaykmewknevdvesgpgqpltslaahskegglksmentioning
confidence: 98%
See 2 more Smart Citations
“…This indicated that NHE gene regulation may be species specific. However, no careful quantitation of the amount of NHE-2 protein along the horizontal intestinal axis has been reported (Zachos et al, 2005). The different distribution of transporters along the intestinal axis from proximal to distal may be due to the unique morphological characteristics of the intestine and substrates, even though further research is needed to confirm this.…”
Section: Mgttvlnlqprarrflpeqfskkapqaykmewknevdvesgpgqpltslaahskegglksmentioning
confidence: 98%
“…cDNA encoding nine members of the family (NHE-1, NHE-2, NHE-3, NHE-4, NHE-5, NHE-6, NHE-7, NHE-8 and NHE-9) have been isolated and characterized in human and rodent (Wakabayashi et al, 1997;Zachos et al, 2005). The various NHE isoforms are known to be expressed in a tissue-specific manner, and presumably have different physiologic functions (Wakabayashi et al, 1997;Zachos et al, 2005). In the small intestine, three NHE isoforms (NHE-1, NHE-2 and NHE-3) have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nephron, individual NHE isoforms have different functions. These functions are reflected in their differential expression along the segments of the nephron, their localization in renal epithelial cells at the basolateral (e.g., isoform NHE1) or apical surface (e.g., isoform NHE3), and their activation in response to distinct agonists [4][5][6][7][8][9][10][11][12][13].…”
Section: Nhementioning
confidence: 99%
“…The putative structure of the mammalian protein with a 10-to 12-transmembrane N-terminus and a largely cytoplasmic C-terminus has been discussed in recent reviews. 9,10 Currently, the structure of the mammalian NHEs is really unknown. Although a low-resolution version of the prokaryotic protein is available, 11 the degree of sequence similarity does not permit homology modeling of the mammalian protein at present.…”
Section: Na + /H + Exchangers In Mammalian Kidneymentioning
confidence: 99%